Development of biodegradable crosslinked urethane-doped polyester elastomers - Dey, J.; Xu, H.; Shen, J.; Thevenot, P.; Gondi, S.R.; Nguyen, K.T.; Sumerlin, B.S.; Sumerlin, B.S.; Yang, J.
Traditional crosslinked polyester elastomers are inherently weak, and the strategy of increasing crosslink density to improve their mechanical properties makes them brittle materials. Biodegradable polyurethanes, although strong and elastic, do not fare well in dynamic environments due to the onset of permanent deformation. The design and development of a soft, strong and completely elastic (100
Keywords: BIODEGRADATION; ELASTOMER; SCAFFOLD; BIOCOMPATIBILITY; TISSUE ENGINEERING